Antibiotic susceptibility and production of endotoxin by Ochrobactrum anthropi isolated from environment and from patients with cystic fibrosis - Chmelař, Dittmar; Holý, Ondřej; Kasáková, Iveta; Hájek, Michal; Lazarová, Anna; Gonzalez-Rey, Carlos; Lasák, Jakub; Raclavský, Vladislav; Čižnár, Ivan (Folia microbiologica, 2019)
The aim of this work was to compare production of endotoxin and to determine susceptibility to antibiotics in two groups of specimens-wild-type strains Ochrobactrum anthropi isolated from the environment and the strains isolated from patients with cystic fibrosis. The determination of the endotoxin produced by the test strains was carried on by using a limulus amebocyte lysate test (LAL test). Determination of ATB sensitivity was accomplished by means of a broth dilution method in a microtiter plate (MIC). No significant difference was found between the group of ochrobacters isolated from the environment and the group of ochrobacters isolated from cystic fibrosis patients. Antibiotic sensitivity testing has indicated that the resistance to tigecycline, trimethoprim/sulfamethoxazole, and gentamicin was slightly higher in strains isolated from cystic fibrosis patients in comparison with strains isolated from the environment. In general, most of the test strains were sensitive to most of the antibiotics tested. Significant resistance has been demonstrated for cefotaxime. Resistance was also found for gentamicin in strains number 4 and 7. The MIC was equal to the breakpoint for this antibiotic (8000 mg/L).
Keywords: Limulus Test; Gram-Negative Bacterial Infections; mikrobiální testy citlivosti; dítě; endotoxiny; Adolescent; cystická fibróza; lidé; gramnegativní bakteriální infekce; Anti-Bacterial Agents; bakteriální léková rezistence; Endotoxins; Microbial Sensitivity Tests; Cystic Fibrosis; Ochrobactrum anthropi; Limulus test; Child; antibakteriální látky; Drug Resistance, Bacterial; mladiství; mikrobiologie životního prostředí; Environmental Microbiology; Humans